ANALISIS EXPECTED RETURN DAN STANDAR DEVIASI PADA SAHAM BBTN DAN BBRI - Galih Diaz Triputra; Arya Tajimalela; Ashillah Fauziyyah Prakoso; Hilmy Azhar Farhan (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
The capital market in Indonesia is a key component in supporting economic growth by providing alternative financing for companies and governments. Investing in stocks has become the main choice for many investors thanks to the potential profits it offers, although they also have to face risks due to drastic price changes. This research aims to analyze the performance and risk of stocks included in LQ45, especially in the banking sector listed in the Indonesia Stock Exchange (IDX) during the period of 2019 to 2023. The data source for this research was obtained from the official BEI website and other trusted references. By using the single index method, this study recalculated the expected results and standard deviation to evaluate stock performance. The analysis results show that the shares of PT Bank Tabungan Negara (Persero) Tbk (BBTN.JK) have the highest expected result, which is 6,52%, even though it is accompanied by the biggest risk (standard deviation 2,4865). On the other hand, PT Bank Rakyat Indonesia (Persero) Tbk (BBRI.JK) recorded an expected result of -0,03% with a lower risk level (standard deviation 2,0779). The findings of this study emphasize the strong relationship between results and risks in stock investment which can be used as a guideline for investors in making more appropriate and data-based investment decisions.